Musik Tiban Dalam Ritual Mendatangkan Hujan di Desa Kerjo Kecamatan Karangan Kabupaten Trenggalek - Achmad Lutfi (SELONDING, 2018)
Tiban is a tradition of the people of the village of Kerjo, Karangan, Trenggalek, East Java, which is held every year, especially when a long dry season strikes the area. Tradian Tiban aims to bring rain with the media, namely having to bleed as redeeming human error. The process of making blood come out of the body is done by the offender by whipping each other using whip. The result of the lash will scratch the body so that it becomes a wound so that it bleeds. The village of Kerjo village is a farming community that uses the Tiban facility to bring rain during a long dry season.The method used in this study is a qualitative method which is done by collecting data based on observations, literature, documentation, and interviews. The results of this study can trace a phenomenon that exists in the Tiban ritual that relates to the beliefs of the people. The syncretism that occurred in the Kerjo village community did not make a barrier in the implementation of the art.